Minimum-Layer Drawings of Trees - Debajyoti Mondal; Muhammad Jawaherul Alam; Md. Saidur Rahman (WALCOM'11: Proceedings of the International Workshop on Algorithms and Computation, 2011)
A layered drawing of a tree T is a planar straight-line drawing of T, where the vertices of T are placed on some horizontal lines called layers. A minimum-layer drawing of T is a layered drawing of T on k layers, where k is the minimum number of layers required for any layered drawing of T. In this paper we give a linear-time algorithm for obtaining minimum-layer drawings of trees.